Induced abortions among Chinese adolescent girls - Tian Wang; Lei Si; Quanbao Jiang (BMC, 2023)
Abstract Background Induced abortion among adolescent girls is a global public health issue and a serious challenge in China, but still remains under-examined. We aimed to examine the overall trend and characteristics of induced abortions among Chinese adolescent girls and to investigate the factors associated with induced abortion. Study design Based on the 2017 China Fertility Survey, this study examined the trend and characteristics of induced abortions among adolescent girls with statistical analysis and multiple indicators of descriptive statistics from period and cohort perspectives, including induced abortion proportion and rate, age-specific cumulative proportion, and age-specific cumulative number of induced abortions in adolescent girls. Results Between 1996 and 2016, the proportion and rate of adolescent induced abortions first increased and then decreased, and the mean age at the time of induced abortions among adolescent girls declined. The cumulative proportion of women who had experienced induced abortion at the age of 15-19 in a cohort is less than 2.5% but shows an upward trend. Over 70% of all adolescent induced abortions are premarital. The proportion of women with unintended pregnancy experiences increased and is higher among rural, less educated, and ethnic minority women. Similarly, the prevalence of induced abortion is higher among adolescent girls who live in rural areas, are less educated, and come from ethnic minorities. The cumulative number of induced abortions and premarital abortions increased with later cohorts. Conclusions This study shows an upward trend in adolescent-induced abortion and a decline in the age at the time of the induced abortion. Women in later birth cohort have a higher proportion of having experienced adolescent induced abortion. Adolescent girls who live in rural areas, who are less educated, or who are from ethnic minorities, are more likely to undergo induced abortions at the age of 15-19. More appropriate educational efforts and interventions are urgently needed to reduce the incidence of adolescent induced abortions.